Once upon a time - Lee, Sin Li (2014)
Once Upon A Time is a visual communication project inspired by the local traditional craft scene and applies this inspiration to create a range of children’s play and educational toys. It aims to give traditional crafts a new lease of life, to explore other alternatives of using these crafts in current context. The basis of this study stems from a personal interest in material culture, which is evident in the project with the use of various materials and crafting skills. Using traditional methods of embroidery, paper layering and woodcutting, it seeks to explore new uses of traditional crafts throughout a child's learning journey, where the realm of imagination and fun reigns. The final deliverables are a set of embroidered books, wooden stamps that function as bowling toys, and a paper layered alphabet poster for children to enjoy and play with.